Constitutional Hypostases of Citizenship of the West European Countries - Kuksin, Ivan N.; Markhgeym, Marina V.; Novikova, Alevtina E.; Samsonov, Valerij N.; Tonkov, Evgeniy E. (Journal of History Culture and Art Research, 2017)
In this article, citizenship is considered in its various forms, based on a comparative legal analysis of the texts from the constitutions of Western European countries, taking into account doctrinal developments and the influence of various social phenomena and processes. Being derived from the sovereign public will, citizenship in the constitutional legal doctrine is traditionally treated as a stable legal relationship between a person and a state, expressed in the aggregate of their mutual rights and obligations. An analysis of the constitutional texts of Western European countries showed that citizenship was enshrined in them as a legal relationship, which parties could be states, as well as a state and an individual; citizenship was also enshrined as a constitutional-legal institution with varying degrees of structural and compositional concentration of its norms, as an independent law and a condition for the exercise of other constitutional rights, freedoms and duties. Typical and special constitutional features of the citizenship of Western European countries are shown.